2021
DOI: 10.1002/aisy.202100017
|View full text |Cite
|
Sign up to set email alerts
|

Memristive Crossbar Arrays for Storage and Computing Applications

Abstract: The emergence of memristors with potential applications in data storage and artificial intelligence has attracted wide attentions. Memristors are assembled in crossbar arrays with data bits encoded by the resistance of individual cells. Despite the proposed high density and excellent scalability, the sneak‐path current causing cross interference impedes their practical applications. Therefore, developing novel architectures to mitigate sneak‐path current and improve efficiency, reliability, and stability may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 257 publications
(348 reference statements)
0
66
0
Order By: Relevance
“…To reduce its computational complexity, one notable option is to use in-memory computing that executes searches in an analogue manner. It has recently been shown that the associative memory can be realized by analog in-memory computing based on crossbar arrays of emerging non-volatile memories [36][37][38][39] . Besides improving the computational density and energy efficiency, this paves the way for reducing the computational complexity of the associative memory to O(1).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce its computational complexity, one notable option is to use in-memory computing that executes searches in an analogue manner. It has recently been shown that the associative memory can be realized by analog in-memory computing based on crossbar arrays of emerging non-volatile memories [36][37][38][39] . Besides improving the computational density and energy efficiency, this paves the way for reducing the computational complexity of the associative memory to O(1).…”
Section: Discussionmentioning
confidence: 99%
“…Resistive switching random access memory (RRAM) devices are one of the emerging non-volatile memory (NVM) technologies with two terminal metal/insulator/metal (MIM) structures [1,2]. The simple MIM structures make RRAMs integrated into dense crossbar arrays and traditional, complementary metal-oxide-semiconductors (CMOS) [2]. RRAM stores data by using different resistance states.…”
Section: Introductionmentioning
confidence: 99%
“…These similarities make the RRAM-based neuromorphic computing a promising technology for future artificial intelligence [4]. Additionally, RRAMs show potential for next-generation high-density NVMs, cryogenic computing, and artificial neural computing due to their high programming speed, low-voltage operation, high scalability and simple fabrication/integration processes [1][2][3][4][5]. Even though significant performance improvements in the RRAM device have been achieved, one remaining drawback is the large parameter variability, whose cause has been ascribed to moisture present in the atmospheric environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…The software-driven neuromorphic computing has realized advanced artificial intelligence with supercomputers. [1][2][3][4][5][6][7][8] However, this technology demands huge space volume and superhigh energy dissipation compared with human brain, seriously limits their potential for large-scale application. Such issue is owing to the fundamental constraints in von Neumann computer architecture and the sequential Boolean logic.…”
Section: Introductionmentioning
confidence: 99%